2002
DOI: 10.1016/s0142-9612(02)00240-5
|View full text |Cite
|
Sign up to set email alerts
|

Coating with genetic engineered hydrophobin promotes growth of fibroblasts on a hydrophobic solid

Abstract: Class I Hydrophobins self-assemble at hydrophilic-hydrophobic interfaces into a highly insoluble amphipathic film. Upon self-assembly of these fungal proteins hydrophobic solids turn hydrophilic, while hydrophilic materials can be made hydrophobic. Hydrophobins thus change the nature of a surface. This property makes them interesting candidates to improve physio- and physico-chemical properties of implant surfaces. We here show that growth of fibroblasts on Teflon can be improved by coating the solid with gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 33 publications
0
70
0
2
Order By: Relevance
“…The non-physiological character of these materials often leads to poor integration into human tissue. Growth of fibroblasts on Teflon served as the first model system to improve biocompatibility via hydrophobins Janssen et al 2002Janssen et al , 2004. Class II hydrophobins have also been used to stimulate growth of human embryogenic kidney cells and neural stem cells on solid surfaces via immobilization of collagen or serum proteins (Hou et al 2008;Li et al 2009).…”
Section: Immobilization Of Molecules and Cellsmentioning
confidence: 99%
“…The non-physiological character of these materials often leads to poor integration into human tissue. Growth of fibroblasts on Teflon served as the first model system to improve biocompatibility via hydrophobins Janssen et al 2002Janssen et al , 2004. Class II hydrophobins have also been used to stimulate growth of human embryogenic kidney cells and neural stem cells on solid surfaces via immobilization of collagen or serum proteins (Hou et al 2008;Li et al 2009).…”
Section: Immobilization Of Molecules and Cellsmentioning
confidence: 99%
“…It has been demonstrated that adsorption of hydrophobins onto solid surfaces may be used to change the character (hydrophobic/hydrophilic) of the surface 15 and that they may be used to form biocompatible surfaces for biosensors. 16 The adhesion of hy-drophobins onto the outside of drug particles to form a biocompatible coating has been recently demonstrated, 17 while attachment of hydrophobins to graphene sheets has also been used in the preparation of biomimetic composite materials. 18 Further exploitation of hydrophobins for these and other applications relies on a detailed understanding of their behaviour on a microscopic level, in particular in understanding the effects that control interfacial absorption strength and rates.…”
Section: Introductionmentioning
confidence: 99%
“…Of essential importance was the discovery that hydrophobins hide airborne fungal spores from the human immune system [18]. The potential technical applications of hydrophobins beyond that range from medical, like covering implants to increase their biocompatibility [19], delivery of lipophilic drugs [20], production of biosensors [21], over exfoliation and functionalization of hydrophobic materials, such as graphene for nanomaterials [22] to their use as food ingredients to stabilize foams and emulsions [23,24]. In order to comply with all these different functions a toolbox of hydrophobins with different characteristics, each of them fulfilling certain tasks, has to be made accessible to biotechnology.…”
Section: Discussionmentioning
confidence: 99%